2004
DOI: 10.1213/01.ane.0000118165.70750.78
|View full text |Cite
|
Sign up to set email alerts
|

A Restrictive Use of Both Autologous Donation and Recombinant Human Erythropoietin Is an Efficient Policy for Primary Total Hip or Knee Arthroplasty

Abstract: A limitation of preoperative autologous blood donation (PABD) in nonanemics and the use of recombinant human erythropoietin (EPO) in anemics (baseline hematocrit [Hct] < or = 39%) could be an efficient approach of the cost-benefit ratio of transfusion during primary total hip (THA) or knee (TKA) arthroplasties. We evaluated the consequences on transfusion rates and costs of two different applications of a transfusion policy based on personal requirements during primary THA or TKA. This quality assurance observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 19 publications
0
41
0
2
Order By: Relevance
“…Accordingly, a blood transfusion is often required after TKA. In an attempt to reduce the adverse effects of blood transfusion, many studies have provided various methods, including preoperative autologous donation3-5), use of the call saver19) and fibrinogen concentrates20), subcutaneous suction drainage6), drain clamping7), hypotensive anesthesia8), and other methods17-21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a blood transfusion is often required after TKA. In an attempt to reduce the adverse effects of blood transfusion, many studies have provided various methods, including preoperative autologous donation3-5), use of the call saver19) and fibrinogen concentrates20), subcutaneous suction drainage6), drain clamping7), hypotensive anesthesia8), and other methods17-21).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, continuous efforts have been made to avoid complications associated with allogeneic blood transfusion, which has led to the invention of blood saving strategies including preoperative autologous donation3-5), treatment of preoperative anemia using oral iron therapy, subcutaneous drainage6), drain clamping7), and hypotensive anesthesia8). Lower extremity alignment is one of the paramount factors determining the long-term success of TKA9-11).…”
Section: Introductionmentioning
confidence: 99%
“…Faris and coworkers demonstrated that erythropoietin administered before elective orthopedic surgery can reduce allogeneic transfusions as well [10]. Other studies have shown that erythropoietin may reduce the need for allogeneic blood, raise preoperative hemoglobin, and decrease the need for autologous blood donation [5,12,13,16]. Cushner retrospectively compared PABD to epoetin alpha in anemic patients undergoing total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee replacement surgery, because of its technical features (reduced time of operation, use of tourniquet), actually involves controlled perioperative blood loss. Some Authors have recently questioned the utility of a predeposit programme in reducing the likelihood of allogeneic transfusions in patients undergoing primary unilateral TKA [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%